Обзор Результативности Экологической Деятельности: Таджикистан - United Nations (United Nations, 2006)
Environmental Performance Reviews promote sustainable development throughout Europe. They present detailed studies on the environmental position of each country and examine the framework for environmental policy and management. This evaluation focuses on Tajikistan.